Detect AD Patients by Using EEG Coherence Analysis. (10th February 2014) - Ho, Ming-Chung; Chen, Tsung-Ching; Huang, Chin-Fei; Yu, Cheng-Hsieh; Chen, Jhih-Ming; Huang, Ray-Ying; Ho, Hsing-Chung; Liu, Chia-Ju
Abstract : The purpose of this study is to discriminate mild Alzheimer's disease (AD) patients from the normal aging. The EEG coherence was applied to analyze the data from auditory oddball paradigm to discriminate the differences of corticocortical connections between mild AD patients and healthy subjects. The results showed that the lower values of coherence were performed in mild AD patients than in the normal aging subjects, especially in theta band. The implications and suggestions are shown in this study.